(untitled) (Revista Internacional de Folkcomunicação, 2021)
Against the countless cancellations of cultural events around the globe, the dynamics of the film festival circuit and its representations took on new courses and different perspectives. About these symbolic power relations, the article dives into a brief data record, on the performance and possible adaptations upon the organization of film festivals, during the year 2020, and throughout the global pandemic, that exponentiated the digitization of some structuring processes on international cinematographic circulation. Ultimately, it adds notions of cultural diplomacy to international film festivals. In order to transpose theoretical concepts to contemporary practice and verify, in this way, the influences and consequences of virtualization to the subjectivities and significance of diplomacy and otherness upon interconnected identities in the current global community.